Identification of differentially expressed circular RNAs associated with thymoma. Issue 9 (11th March 2021) - Wu, Qingjun; Luo, Xuanmei; Li, Hexin; Zhang, Lili; Su, Fei; hou, Shifang; Yin, Jian; Zhang, Wei; Zou, Lihui
Abstract: Background: Thymomas and thymic carcinomas are the most common tumor types among anterior mediastinal lesions. However, the relationship between molecular aberrations and thymoma patients are poorly understood, especially abnormal changes in the expression profiles of circRNAs. The purpose of the present study was to investigate the expression profiles of circRNAs in thymoma patients and their possible roles in the pathogenesis of thymoma. Methods: Diseased tissues and surrounding normal thymic tissues in two thymoma patients were collected for circRNA sequencing. The top four upregulated circRNAs were selected as candidates and further validated with RT‐PCR in 20 thymoma patients. Gene ontology and signal transduction network analyses of circRNA‐related mRNAs were performed to analyze the functional properties. Survival analysis of their parental genes were also carried out to evaluate the clinical value of differentially expressed circRNA. Results: A total of 73 circRNAs were differentially expressed in thymoma tissues using high‐throughput sequencing. Among these circRNAs, hsa_circ_0001173, hsa_circ_0007291, hsa_circ_0003550, and hsa_circ_0001947 were significantly upregulated in thymoma tissues compared with normal thymic tissues. We identified that these four circRNA‐related mRNAs were involved in cell–cell adhesion, MAPK pathways, and TNF pathway, which may contribute to the pathological immune disorder in thymoma. Finally, we also found that SCAP (hsa_circ_0007291 parental gene) and AFF2 (hsa_circ_0001947 parental gene) were all significantly related with progression‐free survival (PFS) of thymoma patients in a Kaplan‐Meier plot ( p ‐value <0.05). Conclusions: The expression levels of hsa_circ_0001173, hsa_circ_0007291, hsa_circ_0003550, and hsa_circ_0001947 were significantly upregulated and positively correlated with immune imbalance in thymoma patients. Abstract : The expression levels of hsa_circ_0001173, hsa_circ_0007291, hsa_circ_0003550, and hsa_circ_0001947 were significantly upregulated and positively correlated with immune imbalance in thymoma patients. The discovery of new differentially expressed circRNAs can be used not only as a biomarker for diagnosis, but also as a potential target for the treatment of thymoma.